2015
DOI: 10.1016/j.heares.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Mice with conditional deletion of Cx26 exhibit no vestibular phenotype despite secondary loss of Cx30 in the vestibular end organs

Abstract: Connexins are components of gap junctions which facilitate transfer of small molecules between cells. One member of the connexin family, Connexin 26 (Cx26), is prevalent in gap junctions in sensory epithelia of the inner ear. Mutations of GJB2, the gene encoding Cx26, cause significant hearing loss in humans. The vestibular system, however, does not usually show significant functional deficits in humans with this mutation. Mouse models for loss of Cx26 function demonstrate hearing loss and cochlear pathology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Our study has revealed vestibular deficits in CBA mice exposed to occupationally‐relevant doses of lead. These deficits, which are highly relevant for human pathophysiology, were unmasked via a newly developed multi‐axis test of head stability (Godin et al, ; Lee et al, ), but not by a common but less specific test of vestibular function, the rotarod. The deficits observed in the head stability tests were greater among animals that received higher Pb exposures, and correlated with individual bone Pb levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study has revealed vestibular deficits in CBA mice exposed to occupationally‐relevant doses of lead. These deficits, which are highly relevant for human pathophysiology, were unmasked via a newly developed multi‐axis test of head stability (Godin et al, ; Lee et al, ), but not by a common but less specific test of vestibular function, the rotarod. The deficits observed in the head stability tests were greater among animals that received higher Pb exposures, and correlated with individual bone Pb levels.…”
Section: Discussionmentioning
confidence: 99%
“…Head motion was then sampled at 1 kHz for five minutes. The amount and direction of measured head motion was considered indicative of VCR function (Godin et al, ; Lee et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Cx26 within the epithelial gap junction network begins to occur around embryonic day 16 in mice (Frenz and Van De Water, 2000) and continues for approximately two weeks after birth as mouse hearing matures. As revealed in mouse studies, improper cochlear development is a pathological outcome of Cx26 mutant expression or Cx26 ablation as noted by the deformation of hair cells and disrupted formation of the tunnel of Corti, which is formed by supporting cells (Wang et al, 2009;Mese et al, 2011;Schutz et al, 2011;Inoshita et al, 2014;Anzai et al, 2015;Lee et al, 2015;Zhu et al, 2015;Chen et al, 2018b). A few rare mutations in GJC3 (Cx30.2/Cx29) and GJB3 (Cx31) have also been linked to hearing loss but it is unclear what role these connexins play and even where these connexins are localized in the auditory tract (Wingard and Zhao, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inner ear comprises the cochlea (hearing organ) and the vestibular organ (balancing organ), which are located adjacent to one another and form a fluid-filled cavity with a bony wall. Several recent studies have shown promising effects from photobiomodulation of the cochlea; [8][9][10][11][12][13] however, the effect of photobiomodulation on the vestibular organ is not well understood.…”
Section: Treatment Of Peripheral Vestibular Dysfunction Using Photobimentioning
confidence: 99%